Case Report: A Delayed Diagnosis of Congenital Syphilis—Too Many Missed Opportunities - Khafaja, Sarah; Youssef, Yolla; Darjani, Nidale; Youssef, Nour; Fattah, Captain Mohammad; Hanna-Wakim, Rima (Frontiers in Pediatrics, 2021)
Congenital syphilis remains a significant public health problem nowadays. We describe the presentation of an infant with a delayed diagnosis of congenital syphilis, with a negative initial nontreponemal test. Our aim is to shed light on the incidence of missed prevention, the importance of awareness, maternal screening, and early diagnosis.